Study of Core Shell n-Octyl Cinnamate in Nanoparticles as Antioxidant - Achmad Wildan; Erlita Verdia Mutiara; Erwin Indriyanti; Mighfar Syukur (Journal of Chemical Process and Material Technology, 2023)
AbstractN-octyl cinnamic is a compound that has potential as a drug as an antioxidant, anti- inflammatory, but is constrained by the nature of n-octyl cinnamate which is difficult to dissolve in water, causing low bioavailability in the systemic circulation. To overcome this problem, curcumin is formulated in the form of nanoparticles using chitosan polymer, a derivative of chitin which can be obtained from crab and shrimp shell waste. This study aims to synthesize n-octyl cinnamic nanoparticles using a simple coating method using chitosan and sodium alginate and to evaluate the stability of the nanoparticles in vitro. The characterization of nanoparticles that was carried out included adsorption efficiency tests, particle size determination using a Particle Size Analyzer and morphological observations using a Transmission Electron Microscopy (TEM) tool. The antioxidant activity test was carried out to determine the potential of the synthesized compound using DPPH method. The results showed that the nanoparticle formula contained n-octyl cinnamic composition with an adsorption % of 91.02%. The particle size is 68.1 nm based on particle size analyzer testing with an average size of 519.6 . The morphological observations showed that the particles were spherical in shape with an uneven surface. The n-octyl cyanamate/Alginate/Chitosan nanoparticles have antioxidant activity with an EC50 value of 31.57 ppm. This shows that n-octyl siamate/alginate/chitosan nanoparticles have the potential to be developed as an antioxidant.Keywords: Nanoparticle, Antioxidant, n-Octyl cyanamate/Alginate/chitosan, Synthesis